LEGAL AND ECONOMIC ANALYSIS OF PUBLIC EXPENDITURES IN CONDITIONS OF BUDGET LIMITATIONS - Ćurčić, Mihailo (The Financial Advisor, 2025)
At the beginning of the 20th century, economic theory and practice introduced the institution of public expenditure into finance, with certain restrictions, which gained importance over time. In modern public finance, the starting point is the position that public revenues and public expenditures are of equal importance, since public expenditures have a specific place and function in market-oriented economies. They have the role of satisfying public needs by engaging public expenditure funds. Special attention is paid to the problem of covering public expenditures, which, as a rule, find the necessary funds in public revenues. However, this problem becomes more complex when extraordinary expenditures appear in public finances, in conditions of economic recession and stagnation, which significantly affects the increase in the degree of budget constraint.